Targets of therapy in progressive MS. (October 2017) - Lassmann, Hans
Highly effective anti-inflammatory therapies have so far been developed for patients with relapsing/remitting multiple sclerosis, which also show some benefits in the early progressive stage of the disease. However, treatment options for patients, who have entered the progressive phase, are still limited. Disease starts as an inflammatory process, which induces focal demyelinating lesions in the gray and white matter. This stage of the disease dominates in the relapsing phase, extends into the early stages of progressive disease, and can be targeted by current anti-inflammatory treatments. In parallel, inflammation accumulates behind a closed or repaired blood brain barrier, and this process peaks in the late relapsing and early progressive stage and then declines. Some data suggest that this process may be targeted by immune ablation and hematopoietic stem cell transplantation. In the late stage, inflammation may decline to levels seen in age-matched controls, but age and disease burden–related neurodegeneration ensues. Such neurodegeneration affects the damaged brain and spinal cord, in which functional reserve capacity is exhausted, giving rise to further disability progression. Anti-inflammatory treatments are unlikely to be beneficial in this stage of the disease, but neuroprotective and repair-inducing strategies may still be effective.